Prospective memory deficits in euthymic bipolar disorder patients: A preliminary study. (3rd December 2012) - Zhou, Jing‐Jing; Xiang, Yu‐Tao; Wang, Chuan‐Yue; Zhou, Fu‐Chun; Ungvari, Gabor S.; Dickerson, Faith; Chiu, Helen F.K.; Lai, Kelly Y.C.; Shum, David H.K.; Lee, Edwin; Au, Raymond W.C.; Tang, Wai‐Kwong; et al.
Abstract Introduction Prospective memory refers to the ability to remember to do something in the future. To date, little is known about prospective memory deficits in bipolar disorder (BD) in remission (euthymia). This study examined the nature and correlates of prospective memory in these patients. Methods Forty‐seven euthymic BD patients and 47 matched healthy controls formed the study sample. Socio‐demographic and basic clinical characteristics, prospective memory (Cambridge Prospective Memory Test [CAMPROMPT]), retrospective memory (immediate Logical Memory subtests of the Wechsler Memory Scales‐Revised [WMS‐R]), IQ (Raven's Progressive Matrices) and executive functioning (Wisconsin Card Sorting Test) were measured in all participants; patients' symptoms were rated with the 17‐item Hamilton Depression Rating Scale and the 11‐item Young Mania Rating Scale. Results Patients performed significantly worse on time‐based prospective memory compared to controls. Multivariate analyses revealed that patients' lower score on Raven's Progressive Matrices significantly contributed to poor performance on time‐based prospective memory, whereas lower scores on WMS‐R Logical Memory subtest contributed to poor performance on event‐based prospective memory; in controls, lower education level and older age significantly contributed to poor performance on time‐based and event‐based prospective memory, respectively. Discussion Prospective memory deficits persist in remitted BD patients suggesting that prospective memory impairment constitutes a trait deficit in BD.